Phytochemical investigation of Erythropalum scandens Blume stems: Discovery of erythropalumins A–J and mechanistic insights into the traditional ‘clear-heat’ effects - Quoc-Dung Tran Huynh; Thuy-Tien Thi Phan; Sui-Wen Hsiao; Man-Hsiu Chu; Yun-Han Wang; Ngoc-Thac Pham; Huong-Giang Le; Phuong Vu Luu; Truc-Ly Thi Duong; Dang-Khoa Nguyen; Bien-Thuy Bui Nguyen; Thanh-Hoa Vo; et al. (Phytochemistry, 2026)

In Vitro functional characterization and acute safety assessment of Staphylococcus piscifermentans isolated from fermented climbing perch (Anabas testudineus) - Tuan Thanh Chau; Huong Huynh Lien Ly; Linh Chi Tran; Men Thanh Tran; Trang Thi Xuan Dai (Food and Humanity, 2026)

Shape matters: Mesoporous silica morphology controls the performance of nitric oxide-releasing nanocomposite bioadhesive hydrogels - Dieu Linh Tran; Huyen Thanh Nguyen Anh; Khoa Diem Pham Huynh; Anh Phuong Nguyen Hong; Ngoc Hoi Nguyen; Dai Hai Nguyen (Chemical Engineering Journal, 2026)

First Nationwide Survey of Phthalic Acid Esters (PAEs) in Vietnamese Dust Samples: Insights into Spatial Trends, Indoor–Outdoor Differences and Human Exposure Implications - Tri Manh Tran; Chi Linh Thi Pham; Anh Duy Dao; Huong Quang Le; Ha My Nu Nguyen; Hue Thanh Tran; Chi Thuy Lan Nguyen; Duyen Thi Thuy Nguyen; Anh Quoc Hoang; Long Van Dang; Chau Ngoc Chu; Binh Minh Tu (International Journal of Environmental Research, 2026)

A Bacillus clausii-based biosensor for heavy metal toxicity: Effects of organic substrates on sensitivity and application to electroplating wastewater - Hoang-Duy P. Nguyen; Phuong-Thao T. Le; Duc-Thang Tran; Anh Minh-Nhat Lai; Thanh-Linh H. Duong; Tien-Cuong Hoang; Tang Ba Quang; Nguyen Phuc Thanh Duy; Ta Dang Khoa; Thuy-Phuong T. Pham (International Biodeterioration & Biodegradation, 2026)

First Description of Larval Morphology of Apocryptodon madurensis (Gobiiformes: Oxudercidae: Oxudercinae) from Vietnam - Thanh Trung Tran; Linh Thuy Nguyen; Thuy Thi Ta; Anh Thuy Thi Tran; Donna M. Guarte-Valida; Nam Thanh Nguyen (Thalassas: An International Journal of Marine Sciences, 2026)

Shrimp Aquaculture Under Viral Threats: Insights into Pathogens and Control Strategies - Linh T. T. Le; Thuan Duc Lao; Phuong-Uyen Le; Hoang Anh Tran; Thuy Huyen Ai Le; Phuong Vy Nguyen (Food and Environmental Virology, 2026)

New limonoids and the protective capacity of Vietnamese Azadirachta indica against Vibrio bacteria and white-spot syndrome virus - Le Quan Tran; Hoang Phu Dang; Duy Khang Nguyen Vu; Vu Linh Tran Pham; Thanh Tinh Bui Thi; Phuong Thao Ngo Huynh; Thi Y. Nhi Nguyen (Natural Product Research, 2026)

Novel betaine-ionic liquid modified biochar: Synthesis and application as adsorbent for extraction of fluoroquinolone antibiotics - Linh Dieu Nguyen; Thao-Vy Duong Nguyen; Tam Minh Cao; Mai Anh Nguyen; Phuong Hoang Tran (Journal of Environmental Chemical Engineering, 2026)

Atomic oxophilic yttrium-interspersed ruthenium clusters confined by nitrogen-doped hollow MXene trigger advanced water electrolysis performance - Thanh Hai Nguyen; Penghao Zhu; Nguyen Tram Anh Duong; Phan Khanh Linh Tran; Van An Dinh; Nam Hoon Kim; Duy Thanh Tran; Joong Hee Lee (Chemical Engineering Journal, 2026)

Enhancing lipid accumulation in marine microalgae for sustainable biofuel applications: A review of Nannochloropsis and Tetraselmis - Linh Doan; Anh Q.V. Tran; Quynh K.L. Ong; Khanh G. Huynh; Khoa Tran; Thanh Khoa Phung (Biomass and Bioenergy, 2026)

Circular Utilization of Banana Pseudostems via Decentralized Ambient Pulping for Wrapping Paper in Vietnam: Technical Performance and Environmental Assessment - Nhung Thi-Tuyet Hoang; Au Thi-Tinh Nguyen; Anh Thi-Kim Tran; My-Linh Nguyen; Tien-Vinh Nguyen (Circular Economy and Sustainability, 2026)

First molecular detection of porcine parvovirus 5 in slaughtered pigs from Southern Vietnam - Trung Tran Nguyen; Dieu Thuy Thi Nguyen; Dung Quoc Tran; Diem Thanh Nguyen; Khanh Linh Hoang Nguyen (Archives of Virology, 2026)

An undescribed alkaloid from Crinum latifolium L.: structural elucidation and evaluation of its biological activity - Tuan Anh Hoang Le; Ngo Van Hieu; Nguyen Tien Dat; Vu Thi Trang; Pham Van Cong; Do Thanh Tuan; Vinh Le Ba; Lo Van Xanh; Tran My Linh; Pham Thi Hoe; Le Quynh Lien (Natural Product Research, 2026)

Inhibition of (interstitial) P2Y6 receptors attenuates fibrosis progression - Lena Marie Süß; Anna Petzendorfer; Minh Linh Tran; Bettina Firmke; Anja Süß; Richard Warth; Katharina Anna-Elisabeth Broeker; Anna-Lena Forst (Pflügers Archiv - European Journal of Physiology, 2026)
Chronic kidney disease (CKD) affects over 850 million people worldwide and is characterized by progressive renal fibrosis driven by activated interstitial fibroblasts. Signaling by extracellular nucleotides and P2 receptors plays an important role in renal pathophysiology, yet its contribution to fibroblast activation and fibrosis remains poorly understood. Here, we investigated the expression and function of G q/11 -coupled P2Y receptors in renal interstitial fibroblasts and their involvement in experimental kidney fibrosis. Using highly selective RNA in situ hybridization, we detected P2Y 1 ( P2ry1 ) and P2Y 6 ( P2ry6 ) receptor expression in interstitial fibroblasts. Notably, P2Y 6 expression was markedly upregulated in several experimental mouse models of renal fibrosis. Functional assays in primary cultured renal fibroblasts confirmed G q/11 -coupled P2Y receptor activity, as evidenced by transient intracellular Ca²⁺ elevations upon nucleotide stimulation. Primary cultured renal fibroblasts exhibited enhanced migration in response to extracellular uridine diphosphate (UDP). To assess the contribution of interstitial P2Y 6 receptors to fibrosis progression, we employed an adenine-induced nephropathy model with or without the selective P2Y 6 antagonist MRS2578. Pharmacological inhibition of P2Y 6 significantly reduced the mRNA expression of the myofibroblast marker α-smooth muscle actin and collagen I. Collectively, these findings suggest that upregulated P2Y 6 receptor signaling promotes the transition of resident interstitial cells into myofibroblasts during renal fibrosis, likely by modulating fibroblast migration. Inhibition of P2Y 6 signaling could represent a new strategy for reducing excessive renal fibrosis.

2-oxotetrahydroquinoline derivatives from Abelmoschus sagittifolius flowers - Hieu Nguyen-Ngoc; Tien-Loc Nguyen; Linh Nguyen-Huong; Giang Nam Pham; Tung Pham-Ha-Thanh; Thuy-Linh Nguyen; Huyen Tran-Thi-Thanh; Tu Nguyen-Thi-Thanh (Natural Product Research, 2026)

Process optimization and life cycle assessment of ultrasound-assisted extraction of Mansoa alliacea flowers with prominent anti-obesity effects - Tran Chi Linh; Duy Toan Pham; Nguyen Tan Thanh; Chong Kim Thien Duc (Sustainable Chemistry and Pharmacy, 2026)

Spatial variability in growth patterns and condition factors of Glossogobius olivaceus across Northern and North Central Vietnam - Chi Linh Do; Ha Thanh Nguyen; Chi Quynh Nguyen; Mai Ngoc Tran Nguyen; Hau Duc Tran (Regional Studies in Marine Science, 2026)

Pyridinium alkaloids – a unique class of naturally occurring salt-form secondary metabolites: a comprehensive review of 68 years (1958–mid-2025) - Huu Canh Vo; Duc Trung Le; Minh Canh Nguyen; Le Viet Ha Tran; To Hoang Long; Vinh Han La; Quoc Tuan Le; Quang Ton That; Linh Tran; Khac-Minh Thai; Van-Kieu Nguyen; Huong Thi Thu Le; et al. (Phytochemistry, 2026)

Bioactive-rich extract fractions from immature Nypa fruticans with anti-inflammatory and metabolic effects: Phytochemical profiling and integrated in vitro/in vivo evaluation - Cam Thi Thai; Cuong-Quoc Nguyen; Quang Le Dang; Phuong Vu Luu; Hong Phuong Nguyen; Thi Trang Huyen Nguyen; Bich Kieu Pham; Hoang Thi Ngoc Lien; Thi Ngoc Linh Duong; Gia Han Ly; Sang Kim Thang; Kinh Luong Nguyen; et al. (Biocatalysis and Agricultural Biotechnology, 2026)

Cross-Shore Distribution of Postflexion Mudskipper and Eel Goby Larvae in Nearshore Waters Informs Seine Sampling Design - Thanh Trung Tran; Linh Thuy Nguyen; Mai Nhat Lai; Nam Thanh Nguyen (Thalassas: An International Journal of Marine Sciences, 2026)

A transformer encoder-only framework for multi-horizon wave forecasting with physical and window-length interpretability - Nga Thanh Duong; Nga Quynh Nguyen Tra; Linh Hoang Tran; Hong My Thi Tran; Khiem Quang Tran (Ocean Engineering, 2026)

Hydroclimatic variability and household resilience in a mountain lake tourism destination: a case study of Ba Be National Park, Vietnam - Thi Bich Lien Nguyen; Quoc Lap Kieu; Thanh Huy Chu; Duy Minh Dao; Thi Ngoc Ha Tran; Thuy Linh Vi; Thi Bich Hanh Nguyen (Theoretical and Applied Climatology, 2026)

Efficacy of Lactobacillus plantarum CG02 Against Vibrio parahaemolyticus pVPA3 ‐1 Infection in Whiteleg Shrimp ( Penaeus vannamei ) - Thao Thi Thu Le; Linh Vu Pham Tran; Hanh My Phan; Thao Phuong Huynh Ngo (Journal of Fish Diseases, 2026)
Thirty lactic acid bacteria (LAB) isolates were obtained from the digestive tracts of whiteleg shrimp ( Penaeus vannamei ) and screened for antagonistic activity against Vibrio parahaemolyticus , the causative agent of Acute Hepatopancreatic Necrosis Disease (AHPND). Among these, four isolates demonstrated strong inhibitory effects, producing inhibition zones of 16–20 mm in agar well diffusion assays. These four LAB isolates were reported to cause no shrimp mortality during the feeding trials. Notably, shrimp fed with the isolate CG02 for 4 weeks showed a significantly improved survival ( p V. parahaemolyticus strain pVPA3‐1. Based on 16S rDNA sequencing, the isolate CG02 was identified as Lactobacillus plantarum . To improve its viability, the isolate CG02 was encapsulated into spray‐dried microcapsules. The resulting probiotic powder exhibited high cell viability, with counts of 9 ± 1.45 × 10 8 CFU g −1 after 4 months at room temperature, and 4.11 ± 0.38 × 10 8 CFU g −1 after 8 months at 4°C. When incorporated into shrimp feed, the CG02 powder did not cause any shrimp mortality. Moreover, it provided a relative percent survival (RPS) of 34.78% compared to the control group following the immersion challenge with V. parahaemolyticus . These results highlight the potential of spray‐dried L. plantarum CG02 as a probiotic feed additive for enhancing shrimp health and supporting sustainable aquaculture practices.

Alpha -Glucosidase inhibitory activity and molecular docking analysis of a new biflavan isolated from Impatiens macrantha - Duc Long Le; Ba Thi Cham; Thi Yen Tran; Ha Nguyen Xuan; Ngoc Binh Vo; Nguyen Thi Le Huyen; Tran Ngoc Dan Thanh; Do Van Truong; Quoc Anh Ngo; Nguyen Thi Thuy Linh (Natural Product Research, 2026)

Microplastics in the environment and biota in Vietnam: a review of occurrence, characteristics, sources, and risks - Quynh Anh Tran-Nguyen; Minh Van Vo; Hoai Nhu Y Nguyen; Linh Thao Thi Phan; Mai Thi Le; Mau Trinh-Dang (Environmental Monitoring and Assessment, 2026)

CRISPR/Cas9-Mediated Knockout of the NAD-Dependent Lactate Dehydrogenases for Altered Stereospecific Lactic Acid Production in Lacticaseibacillus paracasei NC4 - Nhat Huy Chu; Hoang Duc Le; Ngoc Tung Quach; Thi Khanh Linh Pham; Ngoc Anh Ho; Thi Hong Ha Nguyen; Xuan Khoi Tran; Bich Ngoc Pham; Hoang Ha Chu (Biochemical Genetics, 2026)

Transcriptome-based development of functional insertion–deletion markers for genetic diversity analysis in gac (Momordica cochinchinensis (Lour.) Spreng.) - Trung Duc Tran; Hang Thi Thu Nguyen; Hoang Nguyen; Linh Thi Tu Le; Huyen Thanh Pham; Eric J. B. von Wettberg; Hoa Thi Lan Nguyen (Genetic Resources and Crop Evolution, 2026)

Assessment of metal exposure in fingernails of patients with nasopharyngeal cancer: a case study in Vietnamese men - Hanh Van Nguyen; Sang Thi Minh Nguyen; Huong Thi Thu Tran; Loan Thi Hong Truong; Dong Van Nguyen; Linh Thi Truc Nguyen; Ba Ngoc Vu; Phuong Truc Huynh (BioMetals, 2026)

Xylocargranosides A‒B and Xylocargranin a from the Mangrove Xylocarpus granatum - Nguyen Phuong Thao; Tran Thi Bich Ha; Kieu Thi Phuong Linh; Pham Thi Mai Huong; Pham Thanh Binh; Vu Thanh Trung; Nguyen The Cuong; Tran Viet Hung; Nguyen Van Thanh (Journal of Natural Medicines, 2026)

Deep learning-based detection of raft aquaculture using Sentinel-1 and Sentinel-2 data - Van Truong Tran; Kinh Bac Dang; Tuan Linh Giang; Thi Ngan Do; Thi Ngoc Dang; Viet Thanh Pham; Vu Viet Quan Du; Cao Huan Nguyen (Applied Geomatics, 2026)

Silent threat in shrimp aquaculture: understanding and controlling Enterocytozoon hepatopenaei - Linh T. T. Le; Thuan Duc Lao; Nguyen Hoai Nguyen; Phuong-Uyen Le; Hoang Anh Tran; Thuy Huyen Ai Le; Phuong Vy Nguyen (Aquaculture International, 2026)

Heat exposure and agricultural workers' health: A global systematic review with implications for Peri-urban and semi-urban Southeast Asia - Nu Quy Linh Tran; Cordia Chu; Hai Phung; Son Nghiem; Huynh Thi Cam Hong Le; Tuyet-Hanh Tran; Dung Phung (Urban Climate, 2026)

Phenolic glycosides from Ligusticum wallichii with cytotoxic activity - Ninh Khac Thanh Tung; Nguyen Thi Tu Oanh; Nguyen Thi Minh Hang; Nguyen Thi Thu Ha; Tran My Linh; Vu Huong Giang; Yohan Seo; SeonJu Park; Nguyen Tien Dat; Nguyen Xuan Nhiem; Hyung Min Kim; Ninh Khac Ban (Phytochemistry Letters, 2026)

Synthesis, characterization, and ethanol vapor sensing characteristics of vanadium-based-MOFs with and without Cu doping - Tan Le Hoang Doan; Tae-Un Kim; Yujin Kim; My Van Nguyen; Ali Mirzaei; Ngoc Xuan Dat Mai; Linh Ho Thuy Nguyen; Hanh-Vy Tran Nguyen; Ha-Van Nguyen; Nhat Minh Quang Tran; Thang Bach Phan; Hyoun Woo Kim; et al. (Chemical Engineering Journal, 2026)

Sustainable recovery of cellulose from lotus seedpods: Integrating process optimization and environmental-preliminary economic analysis - Chong Kim Thien Duc; Nguyen Trong Tuan; Tran Chi Linh; Huynh Vu Thanh Luong; Duy Toan Pham (Bioresource Technology, 2026)

Allelopathic and herbicidal activities of Hedychium forrestii essential oils against major rice weeds - Ho Le Thi; Phung Dang Linh Bao; Truong Trong Vy; Nguyen The Cuong; Hieu Tran-Trung; Dinh Thi Truong Giang; Hieu Nguyen-Ngoc; Hoang Van Trung; Le Duc Giang (Plant Biosystems, 2026)

Partial replacement of soybean meal with fermented corn husk enhances growth, digestive enzymes, immune response, and growth-, immune-, and antioxidant-related gene expression in Nile tilapia (Oreochromis niloticus) reared in biofloc system - Hien Van Doan; Supreya Wannavijit; Khambou Tayyamath; Tran Thi Diem Quynh; Md Afsar Ahmed Sumon; Nguyen Vu Linh; Phisit Seesuriyachan; Yuthana Phimolsiripol; Maria Ángeles Esteban; Enric Gisbert (Aquaculture, 2026)

Passive or active control of an actual building under earthquakes using rolling rim-type TMD: A comparative study - Ngoc-An Tran; N.D. Anh; Ngoc-Linh Nguyen; Hai-Le Bui; Huong Quoc Cao (Soil Dynamics and Earthquake Engineering, 2026)

Hybrid Metaheuristic–ANN for accurate, stable, and generalized breaking wave height prediction - Khiem Quang Tran; Nga Quynh Nguyen Tra; Linh Hoang Tran; Loc Xuan Luu; Nga Thanh Duong (Ocean Engineering, 2026)

Association between maternal exposure to elevated ambient temperatures and adverse birth outcomes, and potential effect modification of sociodemographic and economic factors: A study in Queensland, Australia - Yohani Dalugoda; Nu Quy Linh Tran; Dwan Vilcins; Darsy Darssan; Stacey Pizzino; Dung Phung (Environmental Research, 2026)

Toward real-time high-resolution fluvial flood forecasting: A robust surrogate approach based on overland flow models - Giang V. Nguyen; Chien Pham Van; Vinh Ngoc Tran; Linh Nguyen Van; Giha Lee (Environmental Modelling & Software, 2026)

Gnetum Montanum Markgr. Extract mitigates gouty arthritis by targeting urate crystal-induced NLRP3 inflammasome activation - Duc-Vinh Pham; Hong-Linh Tran; Thu-Hang Nguyen; Thi-Hanh Do; Hoang-Anh Nguyen; Thuy-Duong Nguyen (Journal of Natural Medicines, 2026)

De Novo Transcriptome Analysis Reveals the Primary Metabolic Capacity of the Sponge Xestospongia sp. from Vietnam - Le Bich Hang Pham; Hai Quynh Do; Chi Mai Nguyen; Tuong Van Nguyen; Hai Ha Nguyen; Huu Hong Thu Nguyen; Khanh Linh Nguyen; Thi Hoe Pham; Quang Hung Nguyen; Quang Trung Le; My Linh Tran; Thi Thu Hien Le (Fishes, 2025)
Marine sponges possess complex metabolic systems that support their growth, physiology, and ecological interactions. However, the primary metabolic capacity of the sponge hosts remains incompletely characterized at the molecular level. In this study, we performed de novo transcriptome sequencing of a pooled sample of three individuals of Xestospongia sp. collected in Vietnam, using a high-throughput Illumina sequencing system, to characterize the host-derived metabolic pathways. A total of 43,278 unigenes were assembled, of which 69.15% were functionally annotated using multiple public databases. Functional annotation revealed a broad repertoire of genes associated with core metabolic pathways, including carbohydrate, lipid, and sterol metabolisms, as well as cofactor-related processes. Specifically, complete pathways involved in folate biosynthesis, terpenoid backbone biosynthesis, ubiquinone (Coenzyme Q) metabolism, and steroid biosynthesis were identified, reflecting the independent metabolic framework of the sponge host. Several highly expressed genes related to these pathways, including COQ7, ERG6, NUDX1, QDPR, and PCBD, were detected, and their expression patterns were confirmed by quantitative RT-PCR. Furthermore, protein-based phylogenetic analyses indicated that these genes are closely related to homologous proteins from other sponge species, supporting their host origin. This study provides the first comprehensive transcriptomic resource for Xestospongia sp. from Vietnam, and offers baseline molecular insights into the primary metabolic capacity of the sponge host. These data establish a foundation for future investigations of sponge physiology and host–microbe metabolic partitioning.

Integrative COI Barcoding and Species Delimitation in Echinodermata from Vietnam - Tran My Linh; Nguyen Chi Mai; Pham Thi Hoe; Le Quang Trung; Nguyen Tuong Van; Luu Xuan Hoa; Hoang Dinh Chieu; Pham Tran Dinh Nho; Nguyen Kim Thoa; Le Quynh Lien; Do Cong Thung (Fishes, 2025)
Echinoderms are marine invertebrates that play important roles in structuring marine benthic ecosystems. DNA barcoding has become a valuable tool for species identification; however, reference DNA barcode libraries for echinoderms remain incomplete. This study aims to: (i) develop a COI-5′ reference dataset for echinoderms from Vietnam by integrating DNA barcodes with morphological data; (ii) evaluate species resolution and barcode gaps using multiple analytical approaches; (iii) assess the consistency of species assignments from BOLD and GenBank for echinoderms collected in Vietnam; (iv) make barcode data publicly available to support global reference database development. Thirty-two echinoderm specimens representing 16 species were analyzed for COI-5′ sequences, and BLAST assignments were highly concordant with those from GenBank and BOLD. Integrative validation confirmed that all taxa were monophyletic in the Neighbor Joining Tree, formed single OTUs in Cluster Sequences, and exhibited clear barcode gaps greater than 3% to the nearest-neighbor species. These results provided species-level resolution for 75% and genus-level resolution for 90% of the records. The dataset, spanning four classes, eight orders, and eleven families, enhances barcode coverage and contributes records (ProcessIDs. BINs; GenBank accessions) to public repositories. This study delivers the first curated COI-5′ reference library, supporting regional baselines for taxonomy, conservation, and biodiversity assessment.

Two previously undescribed megastigmane glycosides from the leaves of Sapium discolour and their NO inhibitory activity - Ninh Khac Ban; Phan Thi Thanh Huong; Tran My Linh; Ninh Khac Thanh Tung; Bui Van Thanh; Bui Huu Tai; Phan Van Kiem; Nguyen Phuong Thao (Natural Product Research, 2025)

Phуtoсhemiсаl соnstituents оf Impаtiens siсulifera with nitriс оxide prоduсtiоn аnd alpha-glucosidase inhibitоrу асtivities - Nguуen Thi Thuy Linh; Duc Long Le; Nguyen Thi Thuy Hang; Do Van Truong; Nguyen Thi Le Huyen; Dao Thi Van; Tran Khac Vu; Quoc Anh Ngo (Natural Product Research, 2025)

Molecular identification and evaluation of yield and grain quality of buckwheat varieties in Vietnam - Linh Hong Ta; Duc Thanh Pham; Yen Thi Hoang Le; Trung Duc Tran; Ha Thi Thu Pham; Trung Thanh Nguyen; Tram Bao Tran; Tao Xuan Vu (Vegetos, 2025)

The temporal change in heat-related mortality in relation to the Heat Health Action Plans in the five major cities of Australia - Nguyen Thi Tuong Vy; Nu Quy Linh Tran; Yohani Dalugoda; Nguyen Minh Quoc; Nguyen Ngoc Nhat Thanh; Stacey Pizzino; Dung Phung (Environmental Research, 2025)

Study on the blending of biochar derived from pine bark in lead-contaminated soil to reduce lead (Pb) uptake in selected leafy vegetables - Tran Le Thi Thanh; Nhi Vo Thi Tuyeta; Ngoc T. T. Tran; Linh Tran Thi Hoai; Uyen Nguyen Thi Toa; Ngoc Vu Thi Bao; Nga T. Dinh (Journal of Soils and Sediments, 2025)

Potential risk of P loss in salt-affected acidic soils amended with biochar or compost - Doan Thi Truc Linh; Chau Minh Khoi; Soh Sugihara; Nguyen Thi Kim Phuong; Nguyen Van Sinh; Huynh Mach Tra My; Tran Ba Linh; Dang Duy Minh; Koki Toyota (Journal of Soil Science and Plant Nutrition, 2025)

Monitoring and Assessing EPR Compliance of Producers and Importers To Prevent Free Riders in Developing Countries: the Case of Vietnam - Thi Yen Anh Tran; Thi Nguyen; Sunil Herat; Prasad Kaparaju; Dinh Linh Le (Circular Economy and Sustainability, 2025)
Extended Producer Responsibility (EPR) represents a critical policy instrument for enhancing waste management systems. While Vietnam has initiated a transition from a discretionary to a mandatory EPR framework, significant challenges persist in the effective monitoring and evaluation of compliance by producers and importers; therefore, this study seeks to develop strategic policy recommendations aimed at strengthening regulatory oversight and mitigating free rider behaviour (when individuals benefit from a good or service without contributing to its cost). By using a multimethod approach that combines desk review and focus group discussions to ensure both document-based and stakeholder-informed insights, the research identifies six key strategies to address non-compliance: cross-checking of data, mandatory registration, periodic and random inspections, enforcement of penalties, public disclosure of EPR-related information, and third-party audits. Moreover, the study delineates four fundamental considerations for conducting EPR inspections: the reliability and availability of data, the level of cooperation from obligated companies, the institutional capacity of inspection authorities, and the risks associated with corruption and lack of accountability among enforcement personnel. Furthermore, to support the inspection process, five practical tools are proposed: a standardized reporting form, a violation report form, a documentary checklist for preparatory review, an on-site inspection checklist, and an inspection reporting template. Finally, the study introduces a conceptual framework for assessing EPR compliance among obligated enterprises. These recommendations are intended to inform policy and regulatory development, thereby contributing to a more accountable, transparent, and effective EPR implementation in Vietnam.

Anti- Helicobacter pylori and anti-inflammatory activities of Persea americana leaf extract and its isolated avocadene: a promising natural therapeutic candidate - Thi Nhi Cong Le; Viet Linh Nguyen; Mong Tham Vo; Thi Ngoc Mai Cung; Thi Huyen Nga Tran; Tien-Dung Nguyen-Dinh; Thanh Ngan Nguyen; Huyen Thanh Nguyen Anh; Tien Dung Cong (Natural Product Research, 2025)

Phytochemical investigation of Crinum asiaticum L.: isolation and characterisation of a new dimeric alkaloid and evaluation of acetylcholinesterase inhibition with molecular docking - Le Quynh Lien; Le Ba Vinh; Vu Thi Trang; Ngo Viet Duc; Nguyen Viet Phong; Seo Young Yang; Nguyen Minh Trang; Ngo Van Hieu; Do Thanh Tuan; Nguyen Tien Dat; Tran My Linh; Pham Thi Hoe; et al. (Natural Product Research, 2025)

Insight into the levels of fine particulate matter during 2016–2020 in the two largest cities of Vietnam - Quang Tran Vuong; Phan Quang Thang; Le Van Linh (Environmental Monitoring and Assessment, 2025)

A novel scalable graph neural network for response prediction of structures with different topologies - Viet-Linh Tran; Jaehong Lee (Engineering Structures, 2025)

Green chemistry for synthesizing carbon dots and their application in pollutant treatment and environmental protection - Tran Nam Anh; Nguyen Thi Hien; Hai-Linh Thi Dang; Nguyen Thi Bich Ngoc; Phan Thị Dien; Nguyen Minh Hoang; Nguyen Thi Hanh; Nguyen Thi Ha; Nguyen Manh Khai; Thuy Duong Pham; Van-Duong Dao (Desalination, 2025)

Oleaginous yeasts as a sustainable alternative source of lipids: an investigation into microbial isolation from food sources, fermentation kinetics, fatty acid profiles, and potential health benefits of microbial lipids - Quoc Duy Nguyen; Thi-Van-Linh Nguyen; Thi Tuong Vi Tran; Yunus Khatri; Jayani Chandrapala; Tuyen Truong (Biocatalysis and Agricultural Biotechnology, 2025)

Influence of rice straw mulching on soil available silicate and maize growth in paddy fields affected by saline intrusion in the Mekong River Delta, Vietnam - Huynh Mach Tra My; Chau Minh Khoi; Jason Condon; Edward G. Barrett-Lennard; Brooke Kaveney; Susan Orgill; Dang Duy Minh; Nguyen Thi Kim Phuong; Tran Duy Khanh; Cao Dinh An Giang; Tran Minh Tien; Doan Thi Truc Linh; et al. (Plant and Soil, 2025)
Background and aims In Vietnam, Si accumulator crops like rice and maize crops are commonly rotated, but rice straw is often removed for animal feed. This study assessed whether rice straw mulch could improve soil available Si and maize growth. Methods A field experiment was conducted over three years in two fields with different soil Si levels. Four rice straw mulch levels (0, 3.5, 7, and 10.5 t ha⁻ 1 ) were applied during the maize growing season (Feb–Apr), and repeated for three years. In the 3rd year, soil samples were analyzed for available Si (phosphate buffer extraction) and Si fractions (CaCl 2 -Si, acetic acid-Si, H 2 O 2 -Si, oxalate-Si, and NaOH-Si). Maize yield and Si, N, P, K, and Na uptake were also evaluated. Results At the lower available Si field, rice straw mulch significantly increased the phosphate buffer-Si, CaCl 2 -Si and H 2 O 2 -Si in soil two weeks after sowing whereas the higher available Si field showed no differences among treatments. In contrast, the Si concentration in maize stems and leaves increased notably in the higher rice straw treatments at both sites. Furthermore, a negative correlation was found between Si and Na concentrations in the maize stems and leaves, suggesting that Si may play a role in mitigating Na uptake and reducing Na toxicity. Conclusion This study demonstrated that the application of 7 and 10.5 t ha⁻ 1 crop⁻ 1 of rice straw to fields with low available Si may enhance the soil Si availability, and improve Si, N, P, K uptake and tolerance to salt stress.

Phthalic acid esters (PAEs) in surface water from five tropical estuaries: Spatial distribution, seasonal variations, and mass loads - Thao Thi Nguyen; Chi Linh Thi Pham; Xuyen Thi Nguyen; Anh Quoc Hoang; Duyen Thi Thuy Nguyen; Nhung Thi Ngoc Ho; Nam Duc Vu; Phong Xuan Dang; Long Van Dang; Tri Manh Tran; Tu Binh Minh (Marine Pollution Bulletin, 2025)

Dual-emission carbon dots: Synthesis, applications, advances and challenges - Nguyen Minh Hoang; Nguyen Thi Bich Ngoc; Nam-Anh Tran; Nang Xuan Ho; Hai-Linh Thi Dang; Dang Viet Cuong; Vu Thi Trang; Phan Thi Lan Huong; Phan Thi Thanh Huyen; Muhammad Saqlain Jamil; Sining Yun; Le Tuan Tu; et al. (Journal of Environmental Chemical Engineering, 2025)

Dietary corn silk enhances growth, immunity, and gene expression in Nile tilapia (Oreochromis niloticus) cultured in a biofloc system - Hien Van Doan; Supriya Wannavijit; Khambou Tayyamath; Tran Thi Diem Quynh; Punika Ninyamasiri; Nguyen Vu Linh; Sang Van Vu; Phisit Seesuriyachan; Majid Khanzadeh; Seyed Hossein Hoseinifar (Fish & Shellfish Immunology, 2025)

Ecological Risks Caused by Co-Accumulation of Phthalic Acid Esters and Cyclic Volatile Methylsiloxanes in Water and Sediment from Rao Cai River, Central Vietnam - Ha My Nu Nguyen; Chi Linh Thi Pham; Dong Huu Nguyen; Huong Quang Le; Tri Manh Tran (Water, Air, & Soil Pollution, 2025)

Parabens in Pharmaceuticals, Personal Care Products, and Surface Waters from Vietnam: Concentrations, Source-Sink Profiles, and Health Risk Assessment - Thuy Minh Le; Nguyen Thuy Ta; Quynh Thi Le; Anh Ngoc Nguyen; Phuong Thi Pham; Chi Linh Thi Pham; Mai Thi Dang; Yen Hai Dao; Kim Thi Truong; Anh Hong Duong; Anh Quoc Hoang; Tri Manh Tran; et al. (International Journal of Environmental Research, 2025)

Essential oil from Goniothalamus elegans Ast leaves in Vietnam: chemical composition, nitric oxide inhibition, and xanthine oxidase inhibition activities - Trang Huyen Xuan Hoang; Tuan Quoc Doan; Dien Dinh; Anh Tuan Le; Hoai Thi Nguyen; Linh Thuy Thi Tran (Natural Product Research, 2025)

Safety of Permissive Cardiotoxicity of Trastuzumab in Patients with Breast Cancer: A Systematic Review and Meta-Analysis - Amira Mohamed Taha; Ramez M. Odat; Wesam Abd El-Tawab Moawad; Sara Adel Abdelkader Saed; Basma Ehab Amer; Dang Nguyen; Dalal Salama Salem; Linh Tran; Loay Kassem (Cardiovascular Toxicology, 2025)
Cardiotoxicity is a recognized adverse effect associated with anti-HER2 therapies. The Trastuzumab-mediated cardiac dysfunction is not dose-dependent and lacks ultrastructural changes, allowing potential recovery after a few months. There is no consensus on the management of patients who develop cardiotoxicity. This meta-analysis aims to assess the safety of the permissive cardiotoxicity of Trastuzumab in patients with breast cancer. We searched PubMed, Cochrane Library, and Embase up to October 2023 for retrospective or prospective studies that investigated the safety of Trastuzumab in patients with breast cancer who continued Trastuzumab therapy after asymptomatic ejection fraction (EF) decline. We conducted a pooled meta-analysis for the subsequent cardiac events, cardiac mortality, and all-cause mortality. We assessed the quality of included studies using the Newcastle–Ottawa Scale and ROBIN-1 tool. A total of eight cohort studies (six retrospective and two prospective), comprising 222 patients, were found eligible and were included in our analysis. The pooled incidence of cardiac events, cardiac-related mortality, and all-cause mortality was 18% (95% CI 13% to 24%), 5% (95% CI 2% to 10%), and 8% (95% CI 2% to 28%), respectively. The incidence of symptomatic or severe cardiac events was lower in those who received cardioprotective medications concomitant with Trastuzumab. Most patients received either angiotensin-converting-enzyme inhibitors, beta-blockers, or a combination of both. Continuation of planned Trastuzumab therapy with concomitant use of cardioprotective medications can be a safe and effective approach for breast cancer control in patients with asymptomatic EF decline. Graphical Abstract

Spatial variation in soil C, N, and trace elements in paddy soil across the coastal, inland, and upland regions of central Vietnam - Toan Nguyen-Sy; Linh Phuong Nguyen Thi; Lim Duong Thi; Hanh Do Hong; Phu Tran Thi; Hai Huynh; Diem Uyen Huynh Thi; Uyen Phan Chi (Environmental Monitoring and Assessment, 2025)

Effects of fermented corn cob on growth performance, digestive enzyme, immune response, and gene expression of nile tilapia (Oreochromis niloticus) raised in biofloc system - Hien Van Doan; Supriya Wannavijit; Khambou Tayyamath; Tran Thi Diem Quynh; Punika Ninyamasiri; Nguyen Vu Linh; Sutee Wongmaneeprateep; Channarong Rodkhum; Phisit Seesuriyachan; Yuthana Phimolsiripol; Seyed Hossein Hoseinifar (Fish & Shellfish Immunology, 2025)

Excochinlignan: A new coumarino lignan from Excoecaria cochinchinensis Lour - Huong Thi Thu Le; Phan-Si-Nguyen Dong; Le-Thuy-Thuy-Trang Hoang; Hoai-Vu Nguyen-Si; Hoang-Vinh-Truong Phan; Thi-Minh-Thao Vo; Thi-Tu-Linh Tran; Tin-Thanh Le; Van-Kieu Nguyen (Medicinal Chemistry Research, 2025)

Analysis of Perfluoroalkyl Substances (PFASs) in Settled Dust by Liquid Chromatography with Tandem Mass Spectrometry: Method Validation and Application to Vietnamese House and Road Dusts - Anh Quoc Hoang; Mai Anh Luu; The Hieu Nguyen; Duc Hieu Nguyen; Thi Huyen Trang Luu; Thi Phuong Mai Nguyen; Thi Hong Thuy Do; Hoang Anh Dinh; Linh Trang Nguyen; Thi Lieu Tran; Thi Quynh Hoa Nguyen; Thi Anh Huong Nguyen (Bulletin of Environmental Contamination and Toxicology, 2025)

Morphology and occurrence of early stages of icefishes from the largest estuary of northern Vietnam - Hau Duc Tran; Linh Gia Dinh; Linh Thuy Thi Nguyen (Marine Biodiversity, 2025)

Enhancing anti-inflammatory activity of noni (Morinda citrifolia L.) juice using lactic acid fermentation by Leuconostoc lactis for developing fermented noni microcapsules as a novel nutraceutical supplement - Thanh-Thuy Dang; Thi-Van-Linh Nguyen; Thi Tuong Vi Tran; Vinh-Lam Nguyen; Quoc-Trung Huynh; Anh Duy Do; Phuoc-Bao-Duy Nguyen; Quoc-Duy Nguyen (Biocatalysis and Agricultural Biotechnology, 2025)

Advancing parameter uncertainty quantification in hydrology models through integration of variational inference with a differentiable hydrology framework - Giang V. Nguyen; Chien Pham Van; Linh Nguyen Van; Vinh Ngoc Tran; Younghun Kim; Giha Lee (Stochastic Environmental Research and Risk Assessment, 2025)

Optimizing Extended-release Formulation of l-tetrahydropalmatine Based on In Vivo Outcomes Using Integrated Modeling Approaches - Thi-Phuong-Dung Pham; Huy Minh Dao; Nguyen-My-Linh Pham; Thanh-Vinh Dang; Hoang-Anh Nguyen; Cao-Son Tran; Linh Nguyen Tran; Nguyen-Thach Tung (AAPS PharmSciTech, 2025)

Optimizing surface fermentation conditions for enhancing polysaccharide and β-glucan production in Sanghuangporus vaninii—a newly recorded medicinal mushroom from Vietnam - Thi Hoang Yen Le; Hong Minh Nguyen; Thi Dam Linh Mai; Thi Hoang Anh Dong; Thi Thanh Mai Nguyen; Xuan Tao Vu; Bao Tram Tran (Vegetos, 2025)

Optimization of ultrasound-assisted extraction of Ehretia asperula leaves with antioxidant and anti-diabetic activities and assessment of the process environmental impacts - Chong Kim Thien Duc; Nguyen Trong Tuan; Tran Chi Linh; Huynh Vu Thanh Luong; Duy Toan Pham (Sustainable Chemistry and Pharmacy, 2025)

Application of Weibull distribution and stable energy concept for numerical solutions of random wave heights - Nga Thanh Duong; Loc Xuan Luu; Linh Hoang Tran; Khiem Quang Tran (Dynamics of Atmospheres and Oceans, 2025)

Conamonin A and dihydrochalcones from the whole plants of Conamomum rubidum (Lamxay & N.S.Lý) Škorničk. & A.D. Poulsen showing anti-inflammatory and cytotoxic activities - Hanh Nhu Thi Hoang; Hung Quoc Vo; Linh Thuy Khanh Nguyen; Linh Thuy Thi Tran; Hoai Thi Nguyen; Ty Viet Pham; Hieu Trung Le; Cuong Viet Canh Le; Bao Chi Nguyen; Duc Viet Ho (Natural Product Research, 2025)

Fermentation of Ngoc Linh ginseng (Panax vietnamensis Ha et Grushv.) root extract using Levilactobacillus brevis QD-1: Changes in majonoside R2 content and pharmacological activities - Quoc-Duy Nguyen; Thi-Van-Linh Nguyen; Thi Tuong Vi Tran; Ngoc-Han Ngo-Thi; Hong-Tham Truong-Thi; Vinh-Lam Nguyen; Trong Khoa Luong; Anh Duy Do (Food Research International, 2025)

Isolating, Screening, and Optimizing Antioxidant Production of Endophytic Bacteria From Zingiber officinale Roscoe (Ginger) - Trang Thi Xuan Dai; Tuan Thanh Chau; Linh Chi Tran; Ta Lam Tai (Current Microbiology, 2025)

Elemental Composition of Women's Fingernails: A Comparative Analysis Between Cervical Cancer Patients and Healthy Individuals - Hanh Van Nguyen; Sang Thi Minh Nguyen; Huong Thi Thu Tran; Loan Thi Hong Truong; Dong Van Nguyen; Linh Thi Truc Nguyen; Ba Ngoc Vu; Phuong Truc Huynh (Biological Trace Element Research, 2025)

Chemical constituents from symplocos sumuntia and their anti-inflammatory effect - Tran Thu Huong; Nguyen Van Thong; Tran Anh Quang; Le Huyen Tram; Le Thi Thuy; Nguyen Thi Thuy My; Nguyen Tuan Anh; Nguyen Tuan Hiep; Nguyen Ngoc Linh; Duc-Dat Le; Tran Thu Ha; Bui Van Thanh (Natural Product Research, 2025)

Response to letter to editor re: Tran et al. 2024 (Huang et al.) - Huan Minh Tran; Feng-Jen Tsai; Kang-Yun Lee; Yuan-Hung Wang; Feng-Ming Yang; Shu-Chuan Ho; Hanh Thi My Bui; Linh Nhat Nguyen Hoang; Linh Thi My Bui; Kin-Fai Ho; Kian Fan Chung; Kai-Jen Chuang; et al. (Science of The Total Environment, 2025)

Coumarin glycosides and their α-glucosidase inhibitory effects from Impatiens eberhardtii - Nguyen Thi Thuy Linh; Nguyen Thi Cuc; Trinh Thi Thuy; Tran Duc Quan; Ba Thi Cham; Do Thi Thao; Nguyen Chi Bao; Vu Tien Chinh; Phan Van Kiem; Nguyen Xuan Nhiem; Dang Viet Hung; Nguyen Thi Hoang Anh (Phytochemistry Letters, 2025)

Biochar-phytolith composite from rice straw: A dual-function material for hydrogen sulfide removal and slow-release nutrient delivery - Van M. Dinh; Hue T. Nguyen; Anh M. Nguyen; Hang T. Tran; Duc T. Nguyen; Linh H. Duong; Phuong M. Nguyen; Son V. Tran; Giang H. Le; Huan X. Nguyen; Anh T.Q. Nguyen; Kieu Trang Trinh; et al. (Biomass and Bioenergy, 2025)

Correction: A systematic review with bibliometric analysis of different approaches and methodologies for undertaking flood vulnerability research - Thuy Linh Nguyen; Chisato Asahi; Thi An Tran (Sustainable Water Resources Management, 2025)

Corrigendum to ‘Extreme temperature increases the risk of COPD morbimortality: A systematic review and meta-analysis [Science of The Total Environment, Vol 958 [2025] 178087’ - Huan Minh Tran; Feng-Jen Tsai; Kang-Yun Lee; Yuan-Hung Wang; Feng-Ming Yang; Shu-Chuan Ho; Hanh Thi My Bui; Linh Nhat Nguyen Hoang; Linh Thi My Bui; Kin-Fai Ho; Kian Fan Chung; Kai-Jen Chuang; et al. (Science of The Total Environment, 2025)

Development of a bioreactor with an integrated non-dispersive infrared CO2 sensor for rapid and sensitive detection of Cr(VI) toxicity in water - Thanh-Truc H. Phan; Hoang-Duy P. Nguyen; Nguyen-Phuong Nguyen; Hong-Nhung Nguyen; Thanh-Linh H. Duong; Boi-An Tran; Tang Ba Quang; Nguyen Phuc Thanh Duy; Ta Dang Khoa; Thuy-Phuong T. Pham (Journal of Hazardous Materials, 2025)

Can we mitigate tropical cyclone formation using aerosols? A review of cyclogenesis and aerosol effects as a theoretical basis - Thao Linh Tran; Roslyn Prinsley; Daniel Rosenfeld; Helen Cleugh; Jiwen Fan (Atmospheric Research, 2025)

Risk association of Lawsonia intracellularis in commercial swine farms - Jittra Jinanan; Jasna Bosnjak-Neumüller; Tobias Steiner; Anh Phong Van Nguyen; Tram Ngoc Thi Ngo; Kieu Thi Nguyen; Linh Ngoc My Tran; Ngoc Minh Le; Toa Hoang Le; Hai Van Nguyen; Danh Cong Lai; Keatipong Mongkolwit; et al. (Tropical Animal Health and Production, 2025)

Two new flavonoids with antimicrobial activity from the roots of Byttneria aspera Colebr. ex Wall (Malvaceae) - Bich Ngan Truong; Thi Mai Huong Doan; Thuy Linh Nguyen; Van Nam Vu; Van Hieu Tran; Marc Litaudon; Van Cuong Pham (Natural Product Research, 2025)

Assessing the impact of individual exposure to air pollution via biomarkers in sputum of children in Ho Chi Minh city, Vietnam - Linh Le Tran; An Le Pham; Minh Duc Do; Quynh Nhat Nguyen; Hieu K.T. Ngo; Hong H.T.C. Le; Vinh Nhu Nguyen; Dung Phung; Peter D. Sly; Phong K. Thai (Environmental Pollution, 2025)

Optimization of the extraction protocol to uptake the flavonoid content from jamaican cherry (Muntingia calabura L.) leaves extract as a source for an antifungal bioproduct development - Nghi Thi Mong Pham; Thanh Tan Nguyen; Dung Khanh Nguyen; Ngoc Minh Vo; Minh Thuy To Nguyen; Loc Huynh Tan Ngo; Linh Chi Tran (Biocatalysis and Agricultural Biotechnology, 2025)

Promoting sustainable shrimp farming: balancing environmental goals, awareness, and socio-cultural factors in the Mekong Delta aquaculture - Thanh Tran; Do Vinh Duong; Trung Duc Le; Ho Huu Loc; Le Thi Ngoc Chau; Linh-Thy Le; Xuan-Thanh Bui (Aquaculture International, 2025)

Extreme temperature increases the risk of COPD morbimortality: A systematic review and meta-analysis - Huan Minh Tran; Feng-Jen Tsai; Kang-Yun Lee; Yuan-Hung Wang; Feng-Ming Yang; Shu-Chuan Ho; Hanh Thi My Bui; Linh Nhat Nguyen Hoang; Linh Thi My Bui; Kin-Fai Ho; Kian Fan Chung; Kai-Jen Chuang; et al. (Science of The Total Environment, 2025)

Distribution of Phthalic Acid Esters (PAEs) in Personal Care Products and Untreated Municipal Wastewater Samples: Implications for Source Apportionment and Ecological Risk Assessment - Chi Linh Thi Pham; Ngoc Bich Hoang; Anh Viet Nguyen; Vu Le; Ngoc Minh Thi Tran; Khiet Thanh Pham; Hoa Duc Phung; Ngoc Chau Chu; Anh Quoc Hoang; Tu Binh Minh; Tri Manh Tran (Water, Air, & Soil Pollution, 2025)

Carotane sesquiterpenes from Peperomia pellucida and their anti-infective activities - Quynh-Mai Thi Ngo; Ngan Thi Tran; Phuong Nguyen Thi Thu; Thu Nguyen Thi; Khoa Nguyen Manh; Hung Nguyen Van; Linh Pham Van; Khai Nguyen Van (Natural Product Research, 2024)

Mangrove vegetation changes and shoreline erosion along the central coastline of Vietnam: A study from Quang Ngai province - Bijeesh Kozhikkodan Veettil; Xuan-Linh Tran; Manoela Sacchis Lopes (Environmental Development, 2024)

Relationship between the AGT M235T genetic variant and the characteristics and prognosis of coronary atherosclerosis in patients with acute myocardial infarction - Duy Cong Tran; Minh Duc Do; Linh Hoang Gia Le; Truc Thanh Thai; Sy Van Hoang; Binh Quang Truong (Molecular Biology Reports, 2024)

Unraveling New Genetic Elements Associated with the Morphological Changes and Relative Silicon Content in Rice Using Genome-Wide Association Studies (GWAS) - Giang Son Tran; Quynh Hoa Nguyen; Linh Thi Thuy Nguyen; Huong Mai; Quyen Phan; Minh Ngoc Nguyen; Si Son Tong; Phat Tien Do; Huong Thi Mai To (Journal of Plant Biology, 2024)

Overexpression of a Soybean Cytochrome P450 Gene, GmCYP, Improves Drought and Insect Tolerance in Tobacco - Linh Khanh Chu; Ngoc Thu Le; Huyen Thi Tran; Nhung Hong Nguyen; Quyen Phan; Hoang Ngoc Le; Gary Stacey; Minviluz G. Stacey; Cuong Xuan Nguyen; Ha Hoang Chu; Phat Tien Do (Journal of Plant Biology, 2024)

Novel trans -caffeate hydrazide derivatives: synthesis, inhibition of nitric oxide (NO) production and molecular docking studies - Trinh Thi Thuy; Nguyen Thi Thuy Linh; Hoa Nguyen Thi Thu; Ba Thi Cham; Tran Duc Quan; Thi Thao Do; Nguyen Thi Hoang Anh; Pham Minh Quan; Domenico V. Delfino; Tran Khac Vu (Natural Product Research, 2024)

Tuning the composition of highly stable mixed-metal MOFs by microwave-assisted hydrothermal method for ultra-high selective and simultaneous capture of CO2 and H2S - Manh B. Nguyen; Linh Ho Thuy Nguyen; Hoa Thi Lai; Huan V. Doan; Ngoc Quang Tran; Ngoc Xuan Dat Mai; Lam Dai Tran; Philip Anggo Krisbiantoro; Kevin C.-W. Wu; Tan Le Hoang Doan (Chemical Engineering Journal, 2024)

Mitochondrial DNA analysis reveals urgent conservation needs for the southernmost population of ayu (Plecoglossus altivelis) - Linh Manh Ha; Hau Duc Tran; Hirohiko Takeshima; Kei’ichiro Iguchi (Environmental Biology of Fishes, 2024)

Floating treatment wetlands to improve the water quality of the Hang Bang canal, Ho Chi Minh City, Vietnam: Effect of plant species - Thi-Dieu-Hien Vo; Thi-Kim-Quyen Vo; Pham-Yen-Nhi Tran; Thi-Viet-Huong Dao; Quang-Huy Hoang; Linh-Thy Le; Nhu-Nguyet Phan; Thuy Diem Trang Ngo; Piet N.L. Lens; Xuan-Thanh Bui (Chemosphere, 2024)

Acylphloroglucinol derivatives from the aerial parts of Syzygium borneense and their cytotoxic activities - Thi Van Nguyen; Thi Quynh Do; Marc Litaudon; Thuy Linh Nguyen; Van Nam Vu; Thu Huong Tran; Thi Mai Huong Doan; Van Cuong Pham (Phytochemistry Letters, 2024)

Structure revision and absolute configuration of 5,7- diepi-2α -hydroxyoplopanone and anti-osteoporotic activities of sesquiterpenoids from the rhizomes of Homalomena pendula - Linh Thuy Khanh Nguyen; Hung Quoc Vo; Hanh Nhu Thi Hoang; Thi Van Anh Tran; Hien Minh Nguyen; Ty Viet Pham; Hang Phuong Thi Ngo; Thanh Pham; Duc Viet Ho (Natural Product Research, 2024)

Transfer of natural radionuclides from soil to water spinach (Ipomoea aquatica Forssk) under flooded and unflooded conditions in Hanoi, Vietnam - Thi-Hong Bui; Van-Loat Bui; Van-Hao Duong; Duc-Thang Duong; Ngoc-Thiem Le; Dinh-Khoa Tran; Van-Khanh Tran; Thi-Thuy-Linh Ha; Giang T.T. Phan; Viet-Hoang Tran; Van-Khanh Hoang; Hoai-Nam Tran (Journal of Environmental Radioactivity, 2024)

Chemical composition, anti-inflammatory and cytotoxic activity of essential oils from two Luvunga species ( L. scandens and L. hongiaoensis ) from Vietnam - Diep Trinh Thi; Dung Luong Van; Trung Phung Van; Hoai Nguyen Thi; Thao Do Thi; Uyen Nguyen Thi To; Linh Tran Thi Hoai; Khai Dang Vinh; Thanh Truc Huynh; Tran Le Thi Thanh (Natural Product Research, 2024)

First Record of Eutaeniichthys cf. gilli Jordan & Snyder, 1901 (Actinopterygii: Gobiiformes: Gobiidae) from Vietnam - Thanh Trung Tran; Linh Manh Ha; Yumi Henmi; Son Cong Nguyen; Nam Thanh Nguyen (Thalassas: An International Journal of Marine Sciences, 2024)

Adiponectin Receptor Agonist Effectively Suppresses Hepatocellular Carcinoma Growth - Mai Ly Thi Nguyen; Chi Pham; Van Tran Pham; Phuong Linh Thi Nham; Ba Thang Ta; Dinh Tuan Le; Quoc Vuong Le; Xuan Cuong Hoang; Przemyslaw Bozko; Linh Toan Nguyen; Khac Cuong Bui (Cell Biochemistry and Biophysics, 2024)

Ingestion and adherence of microplastics by estuarine mysid shrimp - Hattaya Jitrapat; Itchika Sivaipram; Ajcharaporn Piumsomboon; Supakij Suttiruengwong; Jiayi Xu; Tuan Linh Tran Vo; Daoji Li (Marine Environmental Research, 2024)

Effectiveness of Integrating Ensemble-Based Feature Selection and Novel Gradient Boosted Trees in Runoff Prediction: A Case Study in Vu Gia Thu Bon River Basin, Vietnam - Oluwatobi Aiyelokun; Quoc Bao Pham; Oluwafunbi Aiyelokun; Nguyen Thi Thuy Linh; Tirthankar Roy; Duong Tran Anh; Ewa Łupikasza (Pure and Applied Geophysics, 2024)

Rapid identification of SARS-CoV-2 strains via isothermal enzymatic recombinase amplification and nanopore sequencing - Diem Hong Tran; Hoang Dang Khoa Do; Hau Thi Tran; Trang Nguyen Minh Pham; Hoang Danh Nguyen; Hoang Thuy Linh; Hoang Quoc Cuong; Minh Thiet Vu; Huong Thi Thu Phung (Archives of Virology, 2024)

Applications of seaweed extracts in agriculture: An Australian perspective - Tony Arioli; Scott W. Mattner; Md Tohidul Islam; Thi Linh Chi Tran; Marianne Weisser; Pia Winberg; David M. Cahill (Journal of Applied Phycology, 2024)
Society depends on food production. However, agricultural productivity is greatly challenged by extreme climate events and volatility. Seaweed extracts (SWE) have a key role in food production and their use is central to improving agricultural productivity by increasing crop tolerance to stress, improving the efficiency of plant nutrient use, and by contributing to sustainable farm practices. The benefits of SWE to crops have previously been reviewed in the context of the northern hemisphere, but not since 2015 in Australia – specific to its crops and unique stressors. This review is focused on the scientific progress since 2015 and insights from Australian research related to: (i) SWE-stimulated plant responses, (ii) field research on SWE, (iii) optimising the use of SWE in agriculture. The review considers the effects of SWE (made from Durvillaea potatorum and Ascophyllum nodosum ) in the field, across crops, seasons, regions, and farming systems in Australia, and research conducted in the laboratory under controlled conditions on model and crop plants at the molecular, cellular, and physiological levels. The results from the review highlight the role of SWE in plant priming responses in laboratory experiments and its association with improved plant tolerance in the field. The review discusses the field effects related to production and fruit quality. The uniqueness of the Australian research is the inclusion of the same SWE in laboratory and field research, and the characterisation of plant responses under challenged and un-challenged conditions. This information provides deeper insights into the actions of SWE and enables growers and agronomists to optimize their field application in Australian agriculture.

Isolating Miliusa velutina endophytic bacteria to generate antioxidants and optimizing culture conditions for antioxidant production - Trang Thi Xuan Dai; Tuan Thanh Chau; Thao Thi Phuong Truong; Linh Chi Tran; Ngan Thi Kim Nguyen (South African Journal of Botany, 2024)

Comparison between U-shaped structural deep learning models to detect landslide traces - Kinh Bac Dang; Cong Quan Nguyen; Quoc Cuong Tran; Hieu Nguyen; Trung Thanh Nguyen; Duc Anh Nguyen; Trung Hieu Tran; Phuong Thao Bui; Tuan Linh Giang; Duc Anh Nguyen; Tu Anh Lenh; Van Liem Ngo; et al. (Science of The Total Environment, 2024)

Enhancement of textile wastewater biodegradation by biofilm formed on carriers by two halo thermophilic photosynthetic purple bacteria - Tran Thi Huyen Nga; Do Thi Lien; Cung Thi Ngoc Mai; Pham Kien Cuong; Nguyen Viet Linh; Nguyen Xuan Canh; Jun Wei Roy Chong; Kuan Shiong Khoo; Le Thi Nhi-Cong; Pau Loke Show (Journal of Water Process Engineering, 2024)

Homalolides C-D, two new sesquiterpenoids from the rhizomes of Homalomena pendula - Linh Thuy Khanh Nguyen; Hanh Nhu Thi Hoang; Thi Van Anh Tran; Hoai Thi Nguyen; Duc Viet Ho (Natural Product Research, 2024)

Effect of ambient air pollution on hospital admission for respiratory diseases in Hanoi children during 2007–2019 - Thi Trang Nhung Nguyen; Tri Duc Vu; Nhu Luan Vuong; Thi Vuong Linh Pham; Tu Hoang Le; Minh Dien Tran; Thuy Linh Nguyen; Nino Künzli; Geoffrey Morgan (Environmental Research, 2024)

The taxonomy of the genus Asclepios Distant (Heteroptera, Gerromorpha, Gerridae), with description of a new species from Vietnam - Anh Duc Tran; Thi Phuong Linh Le; Thi Anh Nguyet Nguyen (Journal of Asia-Pacific Entomology, 2023)

Pilot and full scale applications of floating treatment wetlands for treating diffuse pollution - Thi-Kim-Quyen Vo; Thi-Dieu-Hien Vo; Eleftheria Ntagia; Kotamraju Amulya; Ngoc-Kim-Qui Nguyen; Pham-Yen-Nhi Tran; Nguyen-Thanh-Tung Ninh; Song-Lam Le; Linh-Thy Le; Cong-Sac Tran; The-Luong Ha; Mai-Duy-Thong Pham; et al. (Science of The Total Environment, 2023)

Effects of Ocimum basilicum mucilage on hyperlipidemia and gut microbiota on mice fed a high-fat diet - Duy Nguyen-Le; Cao-Tri Nguyen; Minh-Vu Ngo-Phan; Thuoc Linh Tran; Minh-Duy Phan; Tatsuya Unno; Hieu Tran-Van (Bioactive Carbohydrates and Dietary Fibre, 2023)

Pollution characteristics, associated risks, and possible sources of heavy metals in road dust collected from different areas of a metropolis in Vietnam - Nguyen Duy Dat; Ly Sy Phu Nguyen; Thi-Dieu-Hien Vo; Truc Van Nguyen; Thi Thuy Linh Do; Anh Thi Kim Tran; Nhung Thi-Tuyet Hoang (Environmental Geochemistry and Health, 2023)

Corrigendum to “Coastal environmental changes in Southeast Asia: A study from Quang Nam Province, Central Vietnam” [Reg. Stud. Mar. Sci. 39 (2020) 101420] - Bijeesh Kozhikkodan Veettil; Juliana Costi; Wiliam Correa Marques; Xuan-Linh Tran; Ngo Xuan Quang; Dong Doan Van; Pham Ngoc Hoai (Regional Studies in Marine Science, 2023)

A new cadinane sesquiterpenoid from Eupatorium adenophorum and α-glycosidase and AChE inhibitory activities of a gossypetin acylglucoside - Minh Giang Phan; Ngoc Phuc Dong; Thi Viet Huong Do; Minh Trang Vu; Phuong Linh To; Nghia Vu Nguyen; Thi Thu Thuy Tran; Susumu Kawakami; Hideaki Otsuka (Medicinal Chemistry Research, 2023)

Prevalence and genetic spectrum associated with hereditary colorectal cancer syndromes, the need to improve cancer risk awareness, and family cascade testing in Vietnam - Huu-Thinh Nguyen; Y-Thanh Lu; Duc-Huy Tran; Ba-Linh Tieu; Kien-Trung Le; Truong-Vinh Ngoc Pham; Thanh-Thuy Thi Do; Dinh-Kiet Truong; Hoa Giang; Hung-Sang Tang (Familial Cancer, 2023)

The first maternal genetic study of hunter-gatherers from Vietnam - Huyen Linh Tran; Huong Pham Mai; Dung Le Thi; Nhung Doan Thi; Lam Le Tung; Tung Pham Thanh; Ha Tran Manh; Hung Nguyen Mau; Hoang Ha Chu; Ha Hoang (Molecular Genetics and Genomics, 2023)

Sesquiterpenoids from the rhizomes of Homalomena pendula and their anti-inflammatory activities - Linh Thuy Khanh Nguyen; Hanh Nhu Thi Hoang; Thao Thi Do; Thi Van Anh Tran; Hoai Thi Nguyen; Duc Viet Ho (Natural Product Research, 2023)

Two new antidiabetic xanthones from the twigs of Garcinia oblongifolia - Dzung N. Bui; Ly T. T. Nguyen; Le-Thu T. Nguyen; Ngoc T. N. Ngo; Phuong T. Tran; Hieu T. Nguyen; Linh T. N. Dang; Lien-Hoa D. Nguyen; Binh T. D. Trinh (Natural Product Research, 2023)

Changes in seasonal compound floods in Vietnam revealed by a time-varying dependence structure of extreme rainfall and high surge - Han Wang; Yunqing Xuan; Thi Van Thu Tran; Anaïs Couasnon; Paolo Scussolini; Linh Nhat Luu; Hong Quan Nguyen; Dominic E. Reeve (Coastal Engineering, 2023)

Characterization of reciprocation membrane bioreactor on treatment performance, energy consumption and membrane fouling - Phuong-Thao Nguyen; Duyen Phuc Hanh Tran; Linh-Thy Le; Chitsan Lin; Le Thi Kim Oanh; Van-Tung Tra; Xuan-Thanh Bui (Bioresource Technology, 2023)

A systematic review with bibliometric analysis of different approaches and methodologies for undertaking flood vulnerability research - Thuy Linh Nguyen; Chisato Asahi; Thi An Tran (Sustainable Water Resources Management, 2023)

Impacts of dyke systems on the distribution of benthic invertebrate communities and physicochemical characteristics of surface water in An Giang, Vietnam - Khanh Cong Huynh; Linh Manh Ha; Nam Sy Tran; Thuan Cong Nguyen; Giao Thanh Nguyen; Cong Van Nguyen (Environmental Science and Pollution Research, 2023)

The Prevalence of Heat-related Illnesses and Associated Factors among Rice Farmers in Vietnam - Nu Quy Linh Tran; Son Nghiem; Cordia Chu; Mai Anh Luong; Thi Tu Ho; Dung Phung (Journal of Agromedicine, 2023)

A facile and practical conversion of carbohydrates into HMF using metal chlorides in [DMSO][CholineCl] deep eutectic solvent - Ha Bich Phan; Cam Manh Luong; Trinh Hao Nguyen; Linh Dieu Nguyen; Kim Nguyen Tran; Hang-Thien Thi Nguyen; Phuong Hoang Tran (Biomass and Bioenergy, 2023)

Development of novel parametric wave model for irregular wave height transformation - Khiem Quang Tran; Nga Thanh Duong; Loc Xuan Luu; Linh Hoang Tran; Winyu Rattanapitikon (Ocean Engineering, 2023)

Coastal landscape classification using convolutional neural network and remote sensing data in Vietnam - Tuan Linh Giang; Quang Thanh Bui; Thi Dieu Linh Nguyen; Van Bao Dang; Quang Hai Truong; Trong Trinh Phan; Hieu Nguyen; Van Liem Ngo; Van Truong Tran; Muhammad Yasir; Kinh Bac Dang (Journal of Environmental Management, 2023)

Structurally natural chitosan films decorated with Andrographis paniculata extract and selenium nanoparticles: Properties and strawberry preservation - Quach Thi Thanh Huong; Nguyen Thanh Hoai Nam; Bui Thanh Duy; Hoang An; Nguyen Duy Hai; Hoang Thuy Kim Ngan; Lam Thanh Ngan; Tran Le Hoai Nhi; Dang Thi Yen Linh; Tran Nhat Khanh; Dang Vu Anh Thu; Huu Hieu Nguyen (Food Bioscience, 2023)

Effective aqueous chromate treatment using triethanolamine anacardate coated magnetic nanoparticles - Nghia Tan Bui; Linh Chi Le; Thanh T. Hoang; Hang Thi Nguyen; Ngoc Thi Thanh Tran; Tuan K.A. Hoang (Environmental Research, 2023)

Performance of low flux sponge membrane bioreactor treating industrial wastewater for reuse purposes - My Linh Nguyen; Thi-Dieu-Hien Vo; Nguyen Duy Dat; Van-Truc Nguyen; Anh Thi Kim Tran; Phuong-Thao Nguyen; Xuan-Thanh Bui (Bioresource Technology Reports, 2023)

Genome-wide association study reveals useful QTL and genes controlling the fatty acid composition in rice bran oil using Vietnamese rice landraces - Nga T. P. Mai; Linh Thi Thuy Nguyen; Son Giang Tran; Huong Thi Mai To (Functional & Integrative Genomics, 2023)

Monitoring the secreted profile of PirAvp and PirBvp toxins from Vibrio parahaemolyticus causing acute hepatopancreatic necrosis disease - Ngoc-Diem Duong; Thuy-Dung Mai-Hoang; Khai-Hoan Nguyen-Phuoc; Kim-Yen Thi Do; Nguyet-Thu Thi Nguyen; Thuoc Linh Tran; Hieu Tran-Van (Aquaculture International, 2023)

Orodispersible film incorporating nanoparticulate loratadine for an enhanced oral bioavailability - Khanh Van Nguyen; Thu Kim Dang; Linh Thi Dieu Vu; Nhan Thi Ha; Hieu Duy Truong; Tuan Hiep Tran (Journal of Pharmaceutical Investigation, 2023)

Roles of microalgae-based biofertilizer in sustainability of green agriculture and food-water-energy security nexus - Thanh Ngoc-Dan Cao; Hussnain Mukhtar; Linh-Thy Le; Duyen Phuc-Hanh Tran; My Thi Tra Ngo; Mai-Duy-Thong Pham; Thanh-Binh Nguyen; Thi-Kim-Quyen Vo; Xuan-Thanh Bui (Science of The Total Environment, 2023)

Prediction of breaking wave height by using artificial neural network-based approach - Nga Thanh Duong; Khiem Quang Tran; Loc Xuan Luu; Linh Hoang Tran (Ocean Modelling, 2023)

Antibiotics tetracycline adsorption and flame-retardant capacity of eco-friendly aerogel-based nanocellulose, graphene oxide, polyvinyl alcohol, and sodium bicarbonate - Vy T. Nguyen; Lam Q. Ha; Linh Chau Thi Van; Phuong Thi Bich Huynh; Dang Mao Nguyen; Vinh Phu Nguyen; Thai Hoa Tran; DongQuy Hoang (Journal of Environmental Chemical Engineering, 2023)

Nitrogen source recovery efficiency in the catfish farming zero emission integrated system in Mekong delta, Viet Nam - Tran Trung Kien; Duong Mai Linh; Nguyen Thanh Hung; Nguyen Thi Phuong Thao; Tran Van Thanh; Tran Thi Hieu; Nguyen Viet Thang; Le Thanh Son; Tran Le Luu; Hans Schnitzer; Le Thanh Hai (Journal of Environmental Chemical Engineering, 2023)

Evolution of properties of macadamia husk throughout gasification: Hints for a zero-waste energy production system - Ngoc Linh Vu; Nang Dinh Nguyen; Van Dong Nguyen; Phuong Lan Tran-Nguyen; Hoai Viet Nguyen; Thi Mai Thanh Dinh; Hong Nam Nguyen (Biomass and Bioenergy, 2023)

Multicomponent photocatalysts for synergic removal of antibiotics in aqueous media: a review - Trinh Duy Nguyen; Taeyoon Lee; Thuan Van Tran; Vinh Huu Nguyen; Linh Xuan Nong; Long Giang Bach; Dai-Viet N. Vo (Environmental Chemistry Letters, 2023)

Widespread distribution of phthalic acid esters in indoor and ambient air samples collected from Hanoi, Vietnam - Anh Viet Nguyen; Tu Van Vu; Chi Linh Thi Pham; Viet Ngoc Nguyen; Nguyen Thuy Ta; Anh Quoc Hoang; Tu Binh Minh; Tri Manh Tran (Environmental Science and Pollution Research, 2023)

Revealing riverbed morphological evolution in river system with complexity: The Vietnam Mekong River case study - Tanh T.N. Nguyen; Shih Dong-Sin; Lloyd H.C. Chua; Linh H. Nguyen; Linh H. Ha; An T. Ngo; Ninh V. Luu; Thai V. Huynh; Linh M. Duong; Chau N. Tran (Journal of Hydrology, 2023)

Two-stage preparation of highly mesoporous carbon for super-adsorption of paracetamol and tetracycline in water: Important contribution of pore filling and π-π interaction - Pham Thanh Trung Ninh; Le Thi Ngoc Tuyen; Nguyen Duy Dat; My Linh Nguyen; Nguyen Thanh Dong; Huan-Ping Chao; Hai Nguyen Tran (Environmental Research, 2023)

Carbon dots in environmental treatment and protection applications - Nam-Anh Tran; Nguyen Thi Hien; Nguyen Minh Hoang; Hai-Linh Thi Dang; Do Quang Huy; Tran Van Quy; Nguyen Thi Hanh; Ngoc Hung Vu; Van-Duong Dao (Desalination, 2023)

Lasibidoupins A and B, two new compounds from the stems of Lasianthus bidoupensis V.S. Dang & Naiki - Nguyen Kim Tuyen Pham; Thi Diem Huong Nguyen; Thi Mong Cam Nguyen; Gia Dinh Nguyen; Cong Doan Huynh; Thi Nga Vo; Thi Quynh Trang Nguyen; Thuc Huy Duong; Van Son Dang; Bui Linh Chi Huynh; Thi Ngoc Mai Tran; Tan Phat Nguyen (Natural Product Research, 2023)

Separation and attribution of impacts of changes in land use and climate on hydrological processes - Francis Polong; Khidir Deng; Quoc Bao Pham; Nguyen Thi Thuy Linh; S. I. Abba; Ali Najah Ahmed; Duong Tran Anh; Khaled Mohamed Khedher; Ahmed El-Shafie (Theoretical and Applied Climatology, 2023)

Z-scheme S, B co-doped g-C3N4 nanotube@MnO2 heterojunction with visible-light-responsive for enhanced photodegradation of diclofenac by peroxymonosulfate activation - Manh Dung Nguyen; Thanh Binh Nguyen; Linh Hai Tran; Thuy Giang Nguyen; Is Fatimah; Eko Prasetyo Kuncoro; Ruey-An Doong (Chemical Engineering Journal, 2023)

Cytotoxic and nitric oxide inhibitory activities of triterpenoids from Lycopodium clavatum L. - Vu Huong Giang; Le Thi Thuy; Tran Thi Hong Hanh; Nguyen Xuan Cuong; Le Ba Vinh; Ninh Khac Ban; Tran My Linh; Nguyen Chi Mai; Tran Thu Huong; Nguyen Hai Dang; Hyuncheol Oh; Dong-Sung Lee; et al. (Natural Product Research, 2022)

Retrieval of total suspended solids from remote sensing reflectance in highly eutrophic lakes in Hanoi (Vietnam) - Nguyen Thi Thu Ha; Quang Vinh Pham; Thien Phuong Thao Nguyen; Thuy Linh Nguyen; Dang Quy Tran (International Journal of Remote Sensing, 2022)

Indicator-based approach for flood vulnerability assessment in ancient heritage city of Hoi An, Central Region of Vietnam - Thuy Linh Nguyen; Chisato Asahi; Thi An Tran; Ngoc Hanh Le (Natural Hazards, 2022)

A new framework for damage detection of steel frames using burg autoregressive and stacked autoencoder-based deep neural network - Viet-Linh Tran (Innovative Infrastructure Solutions, 2022)

Investigation of bioactive chemical constituents and anti-cancer activity of ethanol extract of Curcuma singularis Gagnep rhizomes - Chinh Chung Doan; Thanh Long Le; Nguyen Quynh Chi Ho; Thi Linh Giang Tran; Nguyen Tu Linh Le; Quang Dao Vu; Thi Hong Lan La; Viet Cuong Nguyen; Thi Phuong Thao Nguyen; Nghia Son Hoang (Natural Product Research, 2022)

Zoning the suitability of the western Mekong Delta for paddy rice cultivation and aquaculture under current and future environmental conditions - Hue Doan Van; Xuan Ai Tien Thi; Van Linh Le Thi; Thanh To Van; Nhat Truong Pham; Nguyen Tan Phong; Alexandre S. Gagnon; Quoc Bao Pham; Duong Tran Anh (Environmental Monitoring and Assessment, 2022)

Chemical constituents from Lycopodiella cernua and their anti-inflammatory and cytotoxic activities - Vu Huong Giang; Le Thi Thuy; Pham Thi Cham; Le Ba Vinh; Ninh Khac Ban; Tran My Linh; Nguyen Chi Mai; Pham Thi Hoe; Tran Thu Huong; Nguyen Hai Dang; Hyuncheol Oh; Tran Hong Quang (Natural Product Research, 2022)

Assessing the multi-decadal shoreline dynamics along the Purba Medinipur-Balasore coastal stretch, India by integrating remote sensing and statistical methods - SK Ariful Hossain; Ismail Mondal; Sandeep Thakur; Nguyen Thi Thuy Linh; Duong Tran Anh (Acta Geophysica, 2022)

Reticulatin, a novel C 43 -spiroterpenoid from the lichen Parmotrema reticulatum growing in Vietnam - Thuc-Huy Duong; Van-Kieu Nguyen; Jirapast Sichaem; Thanh-Nha Tran; Thanh-Hung Do; Nguyen-Kim-Tuyen Pham; Thi-Anh-Tuyet Nguyen; Thi-Hoai-Thu Nguyen; Dinh-Tri Mai; Ngoc-Hong Nguyen; Bui-Linh-Chi Huynh (Natural Product Research, 2022)

Enhancement of Edwardsiella piscicida infection, biofilm formation, and motility caused by N-acetylneuraminate lyase - Linh Khanh Vo; Nhung Thi Tran; Yurina Kubo; Daichi Sahashi; Masaharu Komatsu; Kazuhiro Shiozaki (Glycoconjugate Journal, 2022)

Assessment of change in the extent of mangrove ecosystems using different spectral indices in Google Earth Engine based on random forest model - Meena Kumari Kolli; Quoc Bao Pham; Nguyen Thi Thuy Linh; Pham Ngoc Hoai; Romulus Costache; Duong Tran Anh (Arabian Journal of Geosciences, 2022)

Parmosidone K, a new meta -depsidone from the lichen Parmotrema tsavoense - Thi-Hoai-Thu Nguyen; Thi-My-Nhung Nguyen; Thanh-Trung Nguyen; Huu-Hung Nguyen; Ngoc-Hong Nguyen; Dinh-Tri Mai; Bui-Linh-Chi Huynh; Cong-Luan Tran; Thuc-Huy Duong (Natural Product Research, 2022)

Ricicomin A, a new alkaloid from the leaves of Ricinus communis Linn - Nguyen Kim Tuyen Pham; Thi Thao Linh Tran; Thuc Huy Duong; Nguyen Tien Trung; Dang Cam Tu Phan; Dinh Tri Mai; Van Kieu Nguyen; Bui Linh Chi Huynh; Thi Anh Tuyet Nguyen; Trong Duc Tran; Thi Ngoc Mai Tran; Tan Phat Nguyen (Natural Product Research, 2022)

FTO-rs9939609 Polymorphism is a Predictor of Future Type 2 Diabetes: A Population-Based Prospective Study - Tran Quang Binh; Duong Tuan Linh; Le Thi Kim Chung; Pham Tran Phuong; Bui Thi Thuy Nga; Nguyen Anh Ngoc; Tran Quang Thuyen; Do Dinh Tung; Bui Thi Nhung (Biochemical Genetics, 2022)

Evaluation of debris flow and landslide hazards using ensemble framework of Bayesian- and tree-based models - Subodh Chandra Pal; Rabin Chakrabortty; Asish Saha; Saeid Khosrobeigi Bozchaloei; Quoc Bao Pham; Nguyen Thi Thuy Linh; Duong Tran Anh; Saeid Janizadeh; Kourosh Ahmadi (Bulletin of Engineering Geology and the Environment, 2022)

Azole‐resistant Aspergillus fumigatus is highly prevalent in the environment of Vietnam, with marked variability by land use type - Tra‐My N. Duong; Thanh‐Van Le; Khanh‐Linh H. Tran; Phuong‐Tuyen Nguyen; Bich‐Phuong T. Nguyen; Thu‐Anh Nguyen; Huong‐Lan P. Nguyen; Bich‐Ngoc T. Nguyen; Matthew C. Fisher; Johanna Rhodes; Guy Marks; Greg J. Fox; et al. (Environmental Microbiology, 2021)
Summary Azole‐resistant environmental Aspergillus fumigatus presents a threat to public health but the extent of this threat in Southeast Asia is poorly described. We conducted environmental surveillance in the Mekong Delta region of Vietnam, collecting air and ground samples across key land‐use types, and determined antifungal susceptibilities of Aspergillus section Fumigati (ASF) isolates and azole concentrations in soils. Of 119 ASF isolates, 55% were resistant (or non‐wild type) to itraconazole, 65% to posaconazole and 50% to voriconazole. Azole resistance was more frequent in A. fumigatus sensu stricto isolates (95%) than other ASF species (32%). Resistant isolates and agricultural azole residues were overrepresented in samples from cultivated land. cyp51A gene sequence analysis showed 38/56 resistant A. fumigatus sensu stricto isolates carried known resistance mutations, with TR 34 /L98H most frequent (34/38).

Health risk assessment related to cyanotoxins exposure of a community living near Tri An Reservoir, Vietnam - Thien An Dao Nguyen; Linh Thi Nguyen; Alexis Enright; Luu Thanh Pham; Hoang Yen Thi Tran; Thai Thanh Tran; Van Ha Thi Nguyen; Dang Ngoc Tran (Environmental Science and Pollution Research, 2021)

Environmental Effects of Trade Openness in the Presence of Structural Breaks: New Insights from 5-ASEAN Developing Countries - Nguyen Van Tran; Linh Thi Thuy Do (Environmental Modeling & Assessment, 2021)

Assessing the potential and hydrological usefulness of the CHIRPS precipitation dataset over a complex topography in Pakistan - Muhammad Shahid; Khalil Ur Rahman; Sajjad Haider; Hamza Farooq Gabriel; Abdul Jabbar Khan; Quoc Bao Pham; Babak Mohammadi; Nguyen Thi Thuy Linh; Duong Tran Anh (Hydrological Sciences Journal, 2021)

Multi sources hydrological assessment over Vu Gia Thu Bon Basin, Vietnam - Abro Mohammad Ilyas; Quoc Bao Pham; Dehua Zhu; Ehsan Elahi; Nguyen Thi Thuy Linh; Duong Tran Anh; Khaled Mohamed Khedher; Mohammad Ahmadlou (Hydrological Sciences Journal, 2021)

Production of recombinant human G-CSF from non-classical inclusion bodies in Escherichia coli - Nguyen Thi My Trinh; Tran Linh Thuoc; Dang Thi Phuong Thao (Brazilian Journal of Microbiology, 2021)

Application of soft computing to predict water quality in wetland - Quoc Bao Pham; Reza Mohammadpour; Nguyen Thi Thuy Linh; Meriame Mohajane; Ameneh Pourjasem; Saad Sh Sammen; Duong Tran Anh; Van Thai Nam (Environmental Science and Pollution Research, 2021)

Biodegradation of natural rubber and deproteinized natural rubber by enrichment bacterial consortia - Lan Huong Nguyen; Hoang Dung Nguyen; P. Thao Tran; Thi Thuong Nghiem; Thi Thanh Nguyen; Viet Linh Dao; Trung Nghia Phan; Anh Kim To; Masashi Hatamoto; Takashi Yamaguchi; Daisuke Kasai; Masao Fukuda (Biodegradation, 2020)

New 3,4 -seco- diterpene and coumarin derivative from the leaves of Trigonostemon flavidus Gagnep - Ninh Khac Ban; Tran My Linh; Nguyen Chi Mai; Bui Huu Tai; Nguyen Xuan Nhiem; Nguyen Huy Hoang; Phan Van Kiem (Natural Product Research, 2020)

A genome-wide association study reveals the quantitative trait locus and candidate genes that regulate phosphate efficiency in a Vietnamese rice collection - Huong Thi Mai To; Khang Quoc Le; Hiep Van Nguyen; Linh Viet Duong; Hanh Thi Kieu; Quynh Anh Thi Chu; Trang Phuong Tran; Nga T. P. Mai (Physiology and Molecular Biology of Plants, 2020)

BiVO4 photocatalysis design and applications to oxygen production and degradation of organic compounds: a review - Trinh Duy Nguyen; Van-Huy Nguyen; Sonil Nanda; Dai-Viet N. Vo; Vinh Huu Nguyen; Thuan Van Tran; Linh Xuan Nong; Thuong Thi Nguyen; Long-Giang Bach; Bawadi Abdullah; Seong-Soo Hong; Tuyen Van Nguyen (Environmental Chemistry Letters, 2020)

Seasonality shift and streamflow flow variability trends in central India - Alban Kuriqi; Rawshan Ali; Quoc Bao Pham; Julio Montenegro Gambini; Vivek Gupta; Anurag Malik; Nguyen Thi Thuy Linh; Yogesh Joshi; Duong Tran Anh; Van Thai Nam; Xiaohua Dong (Acta Geophysica, 2020)

Simple approach for the rapid estimation of BOD5 in food processing wastewater - Le Thi Bao Ngoc; Tran Anh Tu; Luu Thi Thanh Hien; Duong Nhat Linh; Nguyen Tri; Nguyen Phuc Hoang Duy; Hoang Tien Cuong; Pham Thi Thuy Phuong (Environmental Science and Pollution Research, 2020)

Occurrence of endophytic bacteria in Vietnamese Robusta coffee roots and their effects on plant parasitic nematodes - Ha Hoang; Linh Huyen Tran; Trang Hong Nguyen; Duong Anh Thi Nguyen; Ha Hong Thi Nguyen; Ngoc Bich Pham; Phap Quang Trinh; Tjalf de Boer; Abraham Brouwer; Hoang Ha Chu (Symbiosis, 2020)

Cabozantinib exposure–response analyses of efficacy and safety in patients with advanced hepatocellular carcinoma - Linh Nguyen; Sunny Chapel; Benjamin Duy Tran; Steven Lacy (Journal of Pharmacokinetics and Pharmacodynamics, 2019)

RBM15 Modulates the Function of Chromatin Remodeling Factor BAF155 Through RNA Methylation in Developing Cortex - Yuanbin Xie; Ricardo Castro-Hernández; Godwin Sokpor; Linh Pham; Ramanathan Narayanan; Joachim Rosenbusch; Jochen F. Staiger; Tran Tuoc (Molecular Neurobiology, 2019)

Ontogenic Development of Digestive Enzymes of Mud Crab (Scylla paramamosain) During Larval Stages - Tran Nguyen Duy Khoa; Nguyen Thi Mai; Nguyen Khanh Linh; Ly Thi Yen Mi; Faizah Shaharom-Harrison (Thalassas: An International Journal of Marine Sciences, 2019)

Estimating the potential effects of climate change on rice production in Thailand - Nirote Sinnarong; Chi-Chung Chen; Bruce McCarl; Bao-Linh Tran (Paddy and Water Environment, 2019)

Enhancing the accuracy of rainfall-induced landslide prediction along mountain roads with a GIS-based random forest classifier - Viet-Hung Dang; Tien Bui Dieu; Xuan-Linh Tran; Nhat-Duc Hoang (Bulletin of Engineering Geology and the Environment, 2019)

Contamination status and potential release of trace metals in a mangrove forest sediment in Ho Chi Minh City, Vietnam - Tran Thi Thu Dung; Tong My Linh; Tran Bích Chau; Truong Minh Hoang; Rudy Swennen; Valerie Cappuyns (Environmental Science and Pollution Research, 2019)

Chronic low dose ethanol induces an aggressive metastatic phenotype in TRAMP mice, which is counteracted by parthenolide - Katherine L. Morel; Rebecca J. Ormsby; Emma L. Solly; Linh N. K. Tran; Christopher J. Sweeney; Sonja Klebe; Nils Cordes; Pamela J. Sykes (Clinical & Experimental Metastasis, 2018)

Labdane-type diterpenoids from Vitex limonifolia and their antivirus activities - Ninh Khac Ban; Nguyen Thi Kim Thoa; Tran My Linh; Do Thi Trang; Phan Van Kiem; Nguyen Xuan Nhiem; Bui Huu Tai; Chau Van Minh; Jae-Hyoung Song; Hyun-Jeong Ko; Seung Hyun Kim (Journal of Natural Medicines, 2018)

Ablation of BAF170 in Developing and Postnatal Dentate Gyrus Affects Neural Stem Cell Proliferation, Differentiation, and Learning - Tran Tuoc; Ekrem Dere; Konstantin Radyushkin; Linh Pham; Huong Nguyen; Anton B. Tonchev; Guoqiang Sun; Anja Ronnenberg; Yanhong Shi; Jochen F. Staiger; Hannelore Ehrenreich; Anastassia Stoykova (Molecular Neurobiology, 2017)

A new and efficient approach for construction of uridine/uracil auxotrophic mutants in the filamentous fungus Aspergillus oryzae using Agrobacterium tumefaciens-mediated transformation - Khuyen Thi Nguyen; Quynh Ngoc Ho; Loc Thi Binh Xuan Do; Linh Thi Dam Mai; Duc-Ngoc Pham; Huyen Thi Thanh Tran; Diep Hong Le; Huy Quang Nguyen; Van-Tuan Tran (World Journal of Microbiology and Biotechnology, 2017)

Arabidopsis AtNAP functions as a negative regulator via repression of AREB1 in salt stress response - Hye-Yeon Seok; Dong-Hyuk Woo; Linh Vu Nguyen; Huong T. Tran; Vaishali N. Tarte; Syed Muhammad Muntazir Mehdi; Sun-Young Lee; Yong-Hwan Moon (Planta, 2017)

Algal biomass and biodiesel production by utilizing the nutrients dissolved in seawater using semi-permeable membrane photobioreactors - Z-Hun Kim; Hanwool Park; Young-Jin Ryu; Dong-Woo Shin; Seong-Joo Hong; Hai-Linh Tran; Sang-Min Lim; Choul-Gyun Lee (Journal of Applied Phycology, 2015)

Recent progress and challenges in the computer-aided design of inhibitors for influenza A M2 channel proteins - Linh Tran; Ly Le (Medicinal Chemistry Research, 2014)

Strategy in structure-based drug design for influenza A virus targeting M2 channel proteins - Nhut Tran; Linh Tran; Ly Le (Medicinal Chemistry Research, 2013)

Simultaneous Analysis of Multiple Monoclonal Antibody Biotherapeutics by LC-MS/MS Method in Rat Plasma Following Cassette-Dosing - Hongyan Li; Robert Ortiz; Linh T. B. Tran; Hossein Salimi-Moosavi; Jennifer Malella; Christopher A. James; Jean W. Lee (The AAPS Journal, 2013)